Environmental advantages through producing energy from grape stalk pellets instead of wood pellets and other sources - Ferreira, José (2018)
The aim of this study was to quantify and compare the environmental impact of the heat of grape stalk pellets with that of wood pellets and other sources, using the Life Cycle Assessment methodology. The study was carried out using the ISO 14040/44 series standard. The inventory analysis and, subsequently, the impact analysis were performed using the software SimaPro8.4.0. The method chosen for this environmental impact assessment was CML-IA baseline. The results show that heat from grape stalk pellets is more environmentally friendly than heat from wood pellets for 7 out of 11 impact categories, including marine aquatic ecotoxicity, which is considered the most important impact category. A global reduction of 1.6 × 104 or 1.14 × 106 or 1.9 × 106 tonne of CO2 eq emissions could be achieved if the global potential production of grape stalk pellets replaced wood pellets or light fuel oil or hard coal briquettes, respectively, contributing to the achievement of the EU’s objectives.